Survey Of North Sumatera Petanque Athletes' Achievement Motivation After PON XXI 2024 Aceh North Sumatera - Nevria Marbun, Cindy; Ibrahim; Albert Septian Bangun, Edo; silitonga, Gunawan; Irsa Sola Gracia Manalu, Irsa; P Sibarani, Jupiter; Cristian Purba, Jonatan (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
The purpose of the study was to determine the level of achievement motivation of North Sumatra Petanque athletes after PON XXI 2024 Aceh North Sumatra. This research has been carried out since April 2025. The population in this study were North Sumatra petanque athletes. The sample in this study were 20 North Sumatra petanque athletes. The instrument used in this study was an achievement motivation questionnaire which included aspects of intrinsic motivation and aspects of extrinsic motivation. The results of the study showed that the percentage achievement of North Sumatra Petanque athletes after PON XXI 2024 Aceh North Sumatra 20 athletes analyzed based on specifications when viewed from the percentage distribution there were 15 high category athletes of 75%, 3 medium category athletes of 10% and 2 low category athletes of 15%. The percentage achievement of the results of the intrinsic factor research was 0 athletes who were included in the very high category 0%, 18 medium category athletes of 90% and 2 low category athletes of 10%. With the results of the analysis, it can be shown that North Sumatran petanque athletes have moderate intrinsic motivation of 90% after PON XXI 2024 Aceh, North Sumatra. The percentage achievement of extrinsic factor research results is 4 athletes in the high category of 20%, 4 athletes in the medium category of 20% and 12 athletes in the low category of 60%. With the results of the analysis, it can be indicated that North Sumatran petanque athletes have low extrinsic motivation of 60% after PON XXI 2024 Aceh, North Sumatra.